Pembelajaran Matematika dengan Media Quizziz untuk Meningkatkan Motivasi Belajar Siswa Kelas X SMAN 2 Pasuruan - Intan Meilina Aisyah; Aidatul Istifaiyah; Supriyo (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
PTK was conducted at SMAN 2 Pasuruan with one class as the subject of the research. The purpose of the CAR is to increase students' motivation to learn by using Quizziz learning media. The research was conducted in two cycles, with planning, implementation, observation, and reflection as part of it. The results of the study indicate that the use of Quizziz can increase students' desire to learn. Based on the results of the PTK conducted in class X of SMAN 2 Pasuruan on increasing students' learning motivation by using Quizziz learning media in mathematics learning. In cycle 1, the percentage of students' learning motivation was 74%. Furthermore, in the second cycle, the percentage of students' learning motivation was 83%. With this statement, students' learning motivation increased by 9%. With each quiz given, students become more active and compete healthily. The results show that Quizziz can be used as a useful learning tool to encourage students to learn more. This study found that Quizziz can increase students' motivation and have a positive effect on their learning outcomes.